2009
DOI: 10.1021/cn900021z
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Accumulates within Golgi Apparatus in Dopaminergic Cells as Revealed by Synchrotron X-ray Fluorescence Nanoimaging

Abstract: Chronic exposure to manganese results in neurological symptoms referred to as manganism and is identified as a risk factor for Parkinson's disease. In vitro, manganese induces cell death in the dopaminergic cells, but the mechanisms of manganese cytotoxicity are still unexplained. In particular, the subcellular distribution of manganese and its interaction with other trace elements needed to be assessed. Applying synchrotron X-ray fluorescence nanoimaging, we found that manganese was located within the Golgi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
88
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 42 publications
15
88
3
Order By: Relevance
“…While the symptoms of manganism and PD are very similar, the globus pallidus (GP) is the most affected brain region in manganism rather than the SN. 104 Due to the disease similarities, manganese is also thought to play a role in PD and is frequently used in PD models.…”
Section: Applicationsmentioning
confidence: 99%
“…While the symptoms of manganism and PD are very similar, the globus pallidus (GP) is the most affected brain region in manganism rather than the SN. 104 Due to the disease similarities, manganese is also thought to play a role in PD and is frequently used in PD models.…”
Section: Applicationsmentioning
confidence: 99%
“…The cells labelled B,C in this work, were exposed to 300 lM of Mn and cell A was exposed to 300 lM of Mn and brefeldin A, a molecule known to cause the apparent collapse of the Golgi stacks (Carmona et al, 2010).…”
Section: Sample Preparationmentioning
confidence: 99%
“…This type of direct measurement of tissue Mn makes it unique compared to all other imaging methods discussed in this chapter, which image Mn indirectly, as in MRI, or which image effects of Mn exposure on the body's biochemistry, as in PET and SPECT. To date XRF has found its applications in the study of Mn neurotoxicity in single cell imaging, [129][130][131][132] as well as in high-resolution (order of microns) elemental imaging of ex vivo brain slices of rats exposed to Mn. [133][134][135] The generation of an XRF signal begins with the expulsion of a core electron (e.g.…”
Section: X-ray Fluorescencementioning
confidence: 99%
“…131 The same authors, Carmona et al, 136 recently used single cell micro-XRF to compare the cytotoxicity towards dopamine-producing cells of several environmental Mn sources: inorganic compounds of different oxidation state and solubility (MnCl 2 , MnSO 4 , and Mn 2 O 3 ) and organic compounds (MMT, a gasoline additive, and maneb, a diththiocarbamate fungicide). The authors found that maneb exhibited the highest toxicity, followed by MnCl 2 , MnSO 4 and MMT with intermediate toxicity, whereas the insoluble Mn 2 O 3 was the least toxic compound.…”
Section: X-ray Fluorescencementioning
confidence: 99%